Perineurioma of the colon: an uncommon tumor with an unusual location. Report of a case and review of the literature - MOTTA, F.; SPADOLA, S.; BOSCO, A.; APRILE, G.; PIOMBINO, E.; MAGRO, G. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2018)
Perineurioma is a relatively rare benign peripheral nerve sheath tumor composed of cells resembling to normal perineurium.Although this tumor may arise in the context of a nerve (intraneural perineurioma), extraneural perineurioma does occur, frequently involving the soft tissues of the lower and upper extremities, trunk and head and neck. Rarely it has also been reported in visceral organs, including gastrointestinal tract. We herein describe the clinicopathologic features of a rare case of a perineurioma presenting as a polypoid lesion of the sigmoid colon, emphasizing the pathologic diagnostic clues.